This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We will simplify the expression inside the root. 1 − c o s 2 ( x − 2 ) = 2 s i n 2 ( x − 2 ) , therefore 2 s i n 2 ( x − 2 ) = 2 ∣ s i n ( x − 2 ) ∣ . The question wants us to find x → 2 lim x − 2 2 ∣ s i n ( x − 2 ) ∣
In general lim x → 0 x s i n ( x ) = 1 for both left-handed and right-handed limit, but when it involved the absolute value, there will be the deviation as regardless of the value of x , ∣ s i n ( x ) ∣ will always give positive value while x itself may not, thus: x → 0 − lim x ∣ s i n ( x ) ∣ = − 1 ; x → 0 + lim x ∣ s i n ( x ) ∣ = 1 In similar vein x → 2 − lim x − 2 2 ∣ s i n ( x − 2 ) ∣ = − 2 ; x → 2 + lim x − 2 2 ∣ s i n ( x − 2 ) ∣ = 2 therefore x → 2 lim x − 2 1 − c o s 2 ( x − 2 ) is not determined as both sides of the limit yields different result